ROLE OF COMBINATION DRUG THERAPY FOR MANAGEMENT OF HYPERTENSION WITH INCREASING AGE - BIR SINGH, PARTAP; SINGH, SUKHRAJ; GILL, GURPREET KAUR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: In South Asia, hypertension is the third highest factor contributing in public health burden of disease and major risk factor for coronary artery disease especially in women and old age people. The study was aimed to determine the role of gender and age (20–80 years) on severity of hypertension to design an effective schedule for management of hypertension. Methods: The levels of serum cholesterol, triglycerides (TG), high-density lipoprotein (HDL), low-density lipoproteins (LDL), and blood pressure (BP) of 240 hypertensive patients were monitored. Cholesterol, TG, and HDL levels were detected using ERBA Reagent kit of Transasia Bio-medicals LTD by CHOD-PAP, glycerol phosphate oxidase trinder End point, and polyvinyl sulfonic and polyethyleneglycol-methyl ether based methods, respectively. Results: The BP and levels of serum cholesterol, TG and LDL were increased in both the genders after 40 years of age. However, the rise in levels of these parameters was more in females in comparison to males. A hypertension management schedule involving (BP)/Cholesterol lowering drugs and lifestyle changes for period of 60 days showed that combination drug therapy was more effective than monotherapies of same drugs used at higher dosages. Conclusion: Hypertensive patients strictly followed the prescribed healthy food and exercise schedule showed improvement in their BP and lipid profile even with limited drug intervention.